Kehr tube colon fistula - Santos Dubra, Alfonso; Pereyra Borrelli, César (Cirugía del Uruguay, 1972)
A case of colonic fistula caused by the use of Kehr's tube, is described. The reason for presenting a paper on this subject is not only to point out the possibility of this accident, but also tci show the different types of complications that may occur after a choledocotomy. Consequently the advantages of outer drainage of the common bile duct over the so-called ideal choledocotomy, is a.nalyzed: it is easy to perform, and no serious complications ensue, but above ali its post-operatory evolution is safe. The manner in which Kher's tube should be fitted is discussed, together with the precautions for reducing to a minimun accidents derived from its use; the most practica! manner of avoiding them is by preventing the tube from damaging the structures with which it is in contact. The most suitable. time for the removal of the tube is considered: there is a minimun period (about 12 days) and a maximun (over two months); however the longer it is· left, the greater the risk of complications. The authors revise the. complications which may arise from the use of Kehr's tube, though in general it should be pointed out that they are not significant. This is accompanied by a classified list of the different types of accidents and the means of eliminating them. Finally, the paper stresses that the specific purpose of the drainage is to ensure the depletion of the biliary ducts, evaduate the infected bilis and rest the delicate and complex sphincterian apparatus.